Effect of Chitosan Content and Freezing Temperature on The Properties of Freeze-Thawed Hydrogels - Haryanto; Gita Ayu Lestari (Universitas Muhammadiyah Purwokerto, 2026)
Climate change characterized by increasing temperatures and drought frequency has led to decreased agricultural land productivity, especially in areas with limited water availability. One alternative to overcome this problem is the use of hydrogel as a soil moisture retention material which is able to absorb and store water. This study aims to determine the effect of chitosan concentration (1%, 2%, and 3%) and freezing temperatures (–20°C, –30°C, and –40°C) on the physical characteristics of Polyvinyl alcohol (PVA)-chitosan-based hydrogels synthesized using the freeze–thaw method. The parameters analyzed include gel fraction, swelling ratio, and compressive strength. The results showed that most treatments did not have a significant effect on the physical properties of the hydrogel, especially on the gel fraction and compressive strength. The gel fraction values ranged from 8.42% to 23.55% and the compressive strength ranged from 0.0031 MPa to 0.009 MPa. However, variations in temperature and chitosan concentration affect the swelling ratio. The swelling ratio ranged from 12.98% to 27.90%. PVA-chitosan hydrogels composition and a freezing temperature of –20°C showed the highest potential for water retention despite limited mechanical strength. Therefore, this hydrogel still has potential as an alternative planting medium, especially for maintaining soil moisture in dry areas, with the limitation that the formulation and synthesis process need to be further refined.